Complete Penile Necrosis in a Patient With Heparin-induced Thrombocytopenia: A Case Report() - Blais, Anne-Sophie (Urol Case Rep, 2014)
Penile necrosis is a rare condition that has been mostly described in association with diabetes mellitus and end-stage renal disease. We report an unusual case of acute penile necrosis because of heparin-induced thrombocytopenia. A 75-year-old man presented with acute renal failure and experienced cardiac complications during the hospitalization. The patient was treated twice with intravenous heparin. He developed symptoms of penile necrosis 4 days after the reintroduction of heparin. At that moment, the platelet count dropped by 61%, and the analysis of heparin-pf4 antibodies was positive for heparin-induced thrombocytopenia. The patient underwent a total penectomy and a perineal urethrostomy.